The relationship between survival rate and intradialytic blood pressure changes in maintenance hemodialysis patients. (1st January 2017) - Lu, Jiayue; Zhu, Minxia; Liu, Shang; Zhu, Mingli; Pang, Huihua; Lin, Xinghui; Ni, Zhaohui; Qian, Jiaqi; Cai, Hong; Zhang, Weiming
Abstract: Objective: The objective of this study is to investigate the relationship between blood pressure changes and all-cause mortality, and between blood pressure changes and cardiovascular mortality, for maintenance hemodialysis (MHD) patients during dialysis. Methods: Data regarding general condition, biochemical indices, and survival prognosis of MHD patients who were treated at the Shanghai Jiao Tong University School of Medicine-affiliated Renji Hospital from July 2007 to December 2012 were collected, in order to evaluate the relationship between patients' blood pressure changes during hemodialysis and mortality. Results: Among 364 patients, with an average age of 63.07 ± 13.93 years, an average dialysis vintage of 76.00 (range, 42.25–134.00) months, and a follow-up time of 54.86 ± 19.84 months, there were 85 cases (23.4%) of all-cause death and 46 cases (14.2%) of cardiovascular death. All-cause mortality and cardiovascular mortality were lowest (OR, 0.324 and 0.335; 95% CI, 0.152–0.692 and 0.123–0.911; p value, .004 and .032, respectively) in patients whose systolic blood pressure difference (ΔSBP) before and after dialysis was between 7.09 and 14.25 mmHg. Kaplan–Meier analysis indicated that both all-cause mortality and cardiovascular mortality were markedly increased for patients with ΔSBPless than −0.25 mmHg ( p value, .001 and .044, respectively). Cox regression analysis showed that ΔSBP< −0.25 mmHg, hemoglobin concentration, Kt/v and albumin were independent risk factors for all-cause mortality in MHD patients. Conclusions: MHD patients whose blood pressure increased significantly after hemodialysis had a higher risk of dying; ΔSBP, hemoglobin concentration, Kt/v and albumin were independent risk factors for all-cause mortality in MHD patients.